Analisis Dimensi Akuntabilitas Pengelolaan Dana Desa - Hubertus Oja; Putriyani Putriyani (Department of State Administration - Musamus University, 2024)
Accountability can be interpreted as a form of obligation to account for the success or failure of development implementation in achieving a predetermined goal and target, a medium of accountability carried out periodically. Accountability is a benchmark for a government in carrying out its responsibilities in the most significant and minor governments (villages). This study aims to analyze the accountability of village fund allocation in Sumber Harapan Village, Tanah Miring District, Merauke Regency. The method used in this study uses qualitative methods with a descriptive approach, and data collection techniques in this study include observation, interviews, and documentation. Data analysis uses data analysis, reduction, presentation, conclusion, and verification. The results showed that the accountability dimension of village fund management in Sumber Harapan Village, Tanah Mirirng District, Merauke Regency in its implementation has not been maximized due to the lack of transparency from the village government to the community level of Sumber Harapan Village at large, where the community is the beneficiary of the use of village funds.